Bringing the imperial back in: Reconsidering governance in the late Ottoman Empire, 1839–1923 (Part II). Issue 8 (20th July 2021) - Kuehn, Thomas
Abstract: This is the second of two connected articles that survey recent trends in the historical scholarship of Ottoman imperial governance from the beginning of the Tanzimat state building efforts in the 1830s to the end of empire in the early 1920s. In both articles, I examine how historians have answered the question of what was imperial about the ways in which the Ottoman Empire was governed during this period. Throughout this two‐part series, I argue that an approach that pays attention to the capacity to govern, as Jane Burbank and Frederick Cooper put it, "different people differently" through a broad repertoire of rule balancing this politics of difference with the politics of incorporation, is more conducive to bringing out the complexities of late Ottoman governance than teleological assumptions that consider the empire during this period on a linear path towards the nation state. Part I demonstrated that starting from the 1990s, scholarship on the empire's peripheries in Transjordan, Mount Lebanon, Yemen, and Albania was instrumental in reframing the study of late Ottoman governance by taking its imperial dimensions seriously. In Part II, I will continue this line of inquiry by reviewing pioneering studies that located the politics of difference and incorporation across the empire and not just in its peripheral regions. Here, I will also discuss a body of innovative scholarship that uses the analytical lenses of governmentality, techno‐politics, and International Law to shed light on the novel material, logistical, and legal capacities developed by the Ottoman state especially during the Hamidian period. In the final section, I will turn to studies that suggest that practices of Ottoman imperial governance remained relevant for the running of some of the empire's successor states.